Sosialisasi dan Praktik Pemanfaatan Ekstrak Batang Serai Sebagai Spray Anti Nyamuk di Desa Babakan Loa - Syarlisjiswan, Muhammad Ridho; Amalia, Nabila Putri; Ningrum, Dwi Septia; Syaidina, Syalsabila (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2024)
Based on the records of the Pesawaran District Health Office in 2023 there were 129 cases of dengue hemorrhagic fever which increased from the previous year. This can be overcome with the help of the use of synthetic chemicals or anti-mosquito and the like. However, the use of synthetic chemicals over a long period of time can cause various health problems so that a natural-based alternative is needed, namely using lemongrass. Lemongrass plants produce essential oils that contain important chemical compounds, namely Citronella and Geraniol, which function as mosquito repellents that can reduce mosquito resistance. The purpose of this service activity is to provide education about the dangers of dengue fever and prevention tips and socialization about making natural anti-mosquito lemongrass spray. The method used in this service is socialization and practice of utilizing lemongrass stem extract as an anti-mosquito spray. This socialization and practice activity was carried out with the mothers of hamlet 1 Babakan Loa Village. The results of this activity are expected that the counseling participants can make anti-mosquito sprays at their respective homes